Continuity and change in Tanzania's ruling coalition: Legacies, crises and weak productive capacity - Ole Therkildsen; France Bourgouin (Danish Institute for International Studies (DIIS), 2012)
This paper presents analyses of the current composition of Tanzania's ruling coalition, comprised mainly of the ruling party (the CCM), the bureaucracy and the military, of how it has changed over time and of how its funding has evolved. Specifically, it discusses how historical legacies, structural changes in the economy and specific crises have influenced the composition of the ruling coalition, the holding power of its factions and the strategic use of resources to maintain its power. The paper concludes that Tanzania's ruling coalition is presently characterised by conflicts and bargaining among strong factional elites within the ruling coalition and by the increasing power of its lower level factions. Opposition parties are largely excluded from influence and remain weak. Economic entrepreneurs in the formal productive sectors are few and poorly organised. Their relations with the ruling coalition are ambiguous and largely informal, although exchanges of money and rents are of increasing importance in the relationship. Moreover, informal sector entrepreneurs and smallholders in agriculture are largely excluded from the ruling coalition. There is little evidence that the ruling coalition - despite decades of political stability - has used its position to build and strengthen the productive capacity of domestic entrepreneurs.
Keywords: 330; Wirtschaftsförderung; Politische Kultur; Regierungskoalition; Tansania